2014
DOI: 10.3390/md12074200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antitumor Activity of Stellettin B, a Triterpene from Marine Sponge Jaspis stellifera, on Human Glioblastoma Cancer SF295 Cells

Abstract: Stellettin B was isolated from marine sponge Jaspis stellifera. In vitro antitumor activities were investigated on 39 human cancer cell lines. Stellettin B exhibited highly potent inhibition against the growth of a human glioblastoma cell line SF295, with a GI50 of 0.01 μM. In contrast, stellettin B showed very weak inhibitory activity on normal cell lines including HMEC, RPTEC, NHBE and PrEC, with GI50s higher than 10 μM, suggesting its relatively selective cytotoxicity against human cancer cells compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…We previously reported that Stel B inhibited phosphorylation of Akt in SF295 cells15. Therefore, the effect of Stel B on Akt pathway was examined in A549 cells.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported that Stel B inhibited phosphorylation of Akt in SF295 cells15. Therefore, the effect of Stel B on Akt pathway was examined in A549 cells.…”
Section: Discussionmentioning
confidence: 97%
“…In the example of marine sponges, ROS‐mediated apoptosis was induced by 10‐acetylirciformonin B from Ircinia sp. for leukemia HL 60 cells, stellettin B from Jaspis stellifera for glioblastoma cancer SF295 cells, and Polymastia janeirensis extracts for U138MG glioma cells . Therefore, the ROS modulating effect of marine natural products may induce apoptosis for anticancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro assays revealed Stellettin B induced ROS generation in glioblastoma cancer SF295 cells. Phosphorylated Akt levels were also remarkably reduced in Stellettin B treated SF295 cells (Tang et al, 2014). JG6, is a marine-derived oligosaccharide.…”
Section: Ammad Ahmad Farooqi Et Almentioning
confidence: 91%